Bacteriocin and Hemolysin from Streptococcus faecium - Nakagawa, Shizutoshi (1981)
The bacteriocin and hemolysin produced by a Streptococcus faecium strain were partially separated after gel filtration on Ultrogel AcA-22. The molecular weight of bacteriocin was approximately 300,000, and that of hemolysin was 220,000. Non-bacteriocinogenic mutants retained the hemolytic activity. Production of hemolysin required glucose, whereas that of bacteriocin did not.